Dividend Policy of Indonesian State-Owned Enterprises - Wahyuni Rusliyana Sari (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2018)
Abstract The purpose of this research is to identify the factors that influence the dividend policy. The model considered the impact of ownership structure, firm size, growth opportunities, financial leverage, profitability, business risk, age, previous year’s dividends, and global crisis 2008 on dividend payout ratio. Sample in this research is state-owned enterprises listed in Indonesian Stock Exchange between the years from 2004-2013. With using purposive sampling, the total of the sample in this research is 8 state-owned companies. The methodology of this research was multiple regression linier. The result of this research find that firm size, previous year’s dividends, and global crisis 2008 significant to dividend payout ratio. Ownership structure, growth opportunities, financial leverage, profitability, business risk, and age do not have significant to dividend payout ratio. This result indicates that the companies management has to consider firm size, previous year’s dividends, and global crisis 2008 in dividend payout ratio.